NARRATIVE TEXT MATERIAL DEVELOPMENT BASED ON POWERPOINT - Kusuma, Riki Irawan; Sutapa Y, Y. Gatot; Salam, Uray (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was (1) to find out the target needs and learning needs of the eleventh grade students of SMAN 05 Pontianak, (2) to find out the appropriate design of narrative text material for the eleventh grade students of SMAN 05 Pontianak. The type of this research was Delopmental research. The procedures were adapted from ADD Model proposed by Hannafin Peck. ADD stands for Analyze, Design and Develop. The subject of this research was the eleventh grade students of SMAN 05 Pontianak. The model of MacroTense is learning pack which consisted of 3 main menus namely Unit 1, Unit 2 and Extra. Each menu contained materials which supported the lesson that is talking about narrative text as the main topic within the lesson. The combination of the menus were expected to be able to fulfill the students and the teacher needs in learning the topic. Moreover, narrative text material was designed to enhance the students’ motivation, and interest in learning the topic. Narrative text material with its features help the students to improve their basic knowledge about the topic and ease them to understand the topic into the better. Using Narrative text material creates students into independent, self-directed and discipline learners to analyze, collect, and interpret the knowledge or information of the lesson. Using MacroTense helps the teacher to enrich his/her teaching materials regarding the topic as well as replace the text book in traditional teaching. Keywords: Narrative Text, Powerpoint, ADD Model.